Fusarium Crown and Root Rot of Tarragon in California Caused by Fusarium solani - Koike, S T (Plant disease, 2011)
Tarragon, also known as estragon or dragon's-wort (Artemisia dracunculus), is a perennial plant in the Asteraceae. Tarragon is grown for use in cooking as a fresh and dried herb. In May 2010, commercial tarragon grown in a field on California's central coast was affected by a previously undescribed disease. Initial symptoms consisted of chlorosis of leaves and wilting of shoot tips. As the disease progressed, entire shoots and branches turned brown and died. The plant crown epidermis and cortex and the upper cortex of the main roots turned brown with occasional black streaking. Diseased plants died several weeks after the onset of wilting. A Fusarium species was consistently isolated from symptomatic crown and root tissues. On carnation leaf agar (CLA) incubated under lights, the isolates produced stout, slightly curved macroconidia having blunt apical cells. One- and two-celled oval to cylindrical microconidia were abundant and born in false heads on extremely long monophialides. Chlamydospores were present in 1-month-old cultures. On potato dextrose agar incubated under lights, the isolates produced abundant white aerial mycelium with bluish coloration of the culture surface. The isolates were identified as Fusarium solani (2). Pathogenicity tests were conducted using six isolates, with inoculum produced on CLA. For each isolate, 250 ml of a spore suspension (1 × 106 conidia/ml) were poured onto the roots of 10-cm potted tarragon plants. Ten plants were inoculated for each of the six isolates. A control set of tarragon was treated with 250 ml of water. All plants were maintained in a greenhouse set at 24 to 25°C. After 8 weeks, plants inoculated with the spore suspensions began to show wilting and browning of leaves. Crown epidermis and cortex and root cortex tissues were brown; Fusarium solani was reisolated from the crowns and roots. The experiment was repeated and the results were the same. To my knowledge, this is the first report of F. solani causing a crown and root rot disease of tarragon. The disease caused significant damage with approximately 50% of the commercial field affected. The other Fusarium species previously reported on tarragon is an uncharacterized F. oxysporum isolated from roots of plants grown in California (1). References: (1) D. F. Farr and A. Y. Rossman. Fungal Databases. Systematic Mycology and Microbiology Laboratory, ARS, USDA. Retrieved from http://nt.ars-grin.gov/fungaldatabases/ , March 8, 2011, (2) P. E. Nelson et al. Fusarium Species: An Illustrated Manual for Identification. Pennsylvania State University Press, University Park, PA, 1983